PENGARUH KOMITMEN, PERILAKU PEGAWAI, KEMAMPUAN KERJA DAN PENGAWASAN TERHADAP KINERJA PEGAWAI PADA KANTOR WILAYAH DJP SUMATERA UTARA I - Dindin Syahrudin (Universitas Islam Sumatera Utara, 2020)
The formulation of the problem in this study are: How does the effect of commitment, on employee performance at the North Sumatra I DGT Regional Office? How does the influence of employee behavior on employee performance? How does the influence of employee work ability on employee performance? How does the influence of supervision on employee performance? How big is the influence of commitment, employee behavior, work ability and supervision on employee performance at the North Sumatra I DGT Regional Office? . The purpose of this research is: To analyze and determine the effect of commitment to employee performance partially, to determine the effect of employee behavior on employee performance partially, to determine the effect of employee ability to work partially on employee performance, to determine the effect of partial supervision on employee performance, to know the effect of commitment, employee behavior and supervision of employee performance at the North Sumatra DGT Regional Office I. Data analysis technique used is multiple linear regression analysis.The results showed that there was a significant influence between commitment to employee performance, because according to the results of the analysis of t count t-table (3.107 1.67) at n = 76 with a significance level of 95%, there was a significant effect between employee behavior on performance employees, because according to the results of t analysis t-table (5.306 1.67) at n = 76 with a significance level of 95%, there is a significant influence between work ability on employee performance, because according to the results of t analysis t-table (2,161 1.65) at n = 76 with a significance level of 95%, There is a significant influence between supervision on employee performance, because according to the results of t analysis t-table (3,434 1.67) at n = 76 with a level significant 95%, F-count value F table (17.950 2.72) together (multiple) there is a positive and significant effect of commitment, employee behavior, supervision, the performance of large employees influence by 28.8%. Thus the hypothesis proposed is accepted.